Legal Study about Lecturer Concerning Positions in High School And Foundation Organs - Yudi, Permai; Sitorus, Rolib; Berlian, Berlian (Budapest International Research and Critics University, 2021)
Lecturers are professional educators and scientists with the main task of transforming, developing, and disseminating science, technology, and art through education, research, and community service. Professional is a job or activity carried out by a person and becomes a source of income for life that requires expertise, proficiency, or skills that meet certain quality standards or norms and require professional education. Therefore, lecturers are professional and have integrity in carrying out their duties as distributors of knowledge, and are obliged to carry out the Tridarma Pergutuan Tinggi. At this time there are still many lecturers who occupy a position in universities and at the same time in foundation organs, so that lecturers forget the tridharma of higher education and often struggle with the interests of the foundation at the college where the lecturer serves. The Law on Teachers and Lecturers, and Government Regulations concerning Lecturers clearly stipulates what are the duties and obligations of a lecturer, Circular Letter Number 3 of 2021 concerning the Prohibition of Concurrent Positions of Foundation Organs in the Implementation of Higher Education is issued, but in fact there are still many lecturers occupying positions. in the organ of the foundation as well as serving in universities, therefore it is necessary to carry out more in-depth research on what is the basis for lecturers to hold concurrent positions and what are the sanctions if they are proven to have heeded the rules from the government. This research is a normative legal research (doctrinal research). The approach used by the author in writing this law is a legal approach (statue approach) and an analytical approach (analitycal approach).The stages of the research method were carried out, by examining the laws and regulations related to the title of this research, then analyzed and then drew conclusions about the problems and looking for answers in solving dual-function positions at universities and foundations. The targeted output is beyond the mandatory Sinta National Journal 1-6 or at least OJS National journals such as Justiqa Journal at Quality University